Tuning thermoresponsive network materials through macromolecular architecture and dynamic thiol-Michael chemistry. Issue 38 (31st August 2018) - Chakma, Progyateg; Digby, Zachary A.; Via, Jeremy; Shulman, Max P.; Sparks, Jessica L.; Konkolewicz, Dominik
Abstract : Synthesis of precision polymers crosslinked with dynamic thiol-Michael adducts is developed, and the materials are characterized to determine structure–property relationships. Abstract : This work reports synthesis of dynamic materials crosslinked with thiol-Michael linkages with distinct primary polymer architectures. RAFT polymerization allows control over degree of polymerization and macromolecular architecture. Well-defined branched and linear polythiol polymers were synthesized by RAFT and crosslinked using thiol-Michael chemistry. Branched and linear polymeric materials with different crosslink densities were evaluated by size exclusion chromatography, tensile testing, rheology, and differential scanning calorimetry. These materials are elastic and show dynamic behavior ( e.g. healing ability and malleability) in response to thermal stimulus (90 °C) due to the presence of the stimulus responsive thiol-maleimide linkages as crosslinkers along the polymer backbone. The data suggest that materials synthesised by RAFT healed faster than materials of similar weight average chain length and crosslink density synthesized by conventional free radical polymerization. Healing ability and malleability properties of these dynamic materials are dramatically higher than materials crosslinked with static crosslinkers. Small molecular studies of thiol-maleimide adducts indicate the potential of using thiol-Michael linkages in dynamically crosslinked materials. In addition to significant re-healing and malleability properties, these materials showed mechanical stability in creep deformation, stress relaxation, and creep recovery experiments under ambient conditions due to their essentially static nature under these conditions.